1992
DOI: 10.1007/bf01296503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for postprandial release of motilin in humans

Abstract: Plasma concentrations of motilin rise in the first 30 min following the ingestion of a meal in man. To elucidate the mechanisms of this postprandial motilin release, we verified the effect of cerebral stimulation and of gastric distension, both events normally occurring in the early postprandial period, on plasma motilin concentrations. Cerebral stimulation was induced by modified sham feeding (MSF) and gastric distension was done by inflating (with 0, 60, 240, or 480 cc of air) a latex balloon positioned in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…More specifically, it peaks before the onset of activity fronts that starts in the antrum, 11,13 and infusion of motilin can induce activity fronts 10 . It is also released after meal intake, but its role in the postprandial motility is less clear 26,27 . Another effect of motilin in the upper GI tract is to stimulate gallbladder emptying 28 .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it peaks before the onset of activity fronts that starts in the antrum, 11,13 and infusion of motilin can induce activity fronts 10 . It is also released after meal intake, but its role in the postprandial motility is less clear 26,27 . Another effect of motilin in the upper GI tract is to stimulate gallbladder emptying 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It is theoretically possible that in the present study, early antral distension by the cholestyramine‐containing solution might have initiated motilin release and gallbladder contraction. Others have shown that balloon‐induced distension of the gastric fundus could release plasma motilin 32 . However, the fact that intraduodenal cholestyramine administration also greatly enhances gallbladder contraction and pancreatic secretion without significant CCK release, 2 argues against this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the circulating concentration of motilin in blood exhibits a cyclic variation that correlates with changes in duodenal motility. It has been demonstrated that the peak of plasma motilin corresponds to the onset of duodenal phase III activity in the fasting state in animals as well as in humans 16–17 . Because the cycle of motilin release is associated with the cycle of interdigestive motility, great variation in the cycle of motilin release is therefore expected among subjects, as well as within an individual subject.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the lack of correlation between the motilin level in the blood and milk might be attributed to the following factors: (i) the time difference in reflecting postprandial peak levels of motilin in plasma and milk. The motilin level measured in the postprandial state was attributed to a baseline level plus a postprandial increase that peaks at 30 min after the meal 17 . It takes time for motilin to be secreted into milk and this postprandial increase in motilin was therefore not reflected in milk at the time of measurement; and (ii) the difference in half‐life time of motilin in milk and plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation